Effects of magnesium sulfate attack on ordinary portland cement (OPC) mortars - Mohammed Misbahul, Amin; Shamsul Baharin, Jamaludin; Faizul, Che Pa; K.K. Chuen (Portuguese Electrochemical Society, 2009)
Link to publisher's homepage at http://www.scielo.oces.mctes.pt/scielo.php/script_sci_serial/lng_en/pid_0872-1904/nrm_iso